"I will not peace": Language, power, and the Duchess of York in Richard II - Veronica Lowe (Journal of Modern Languages)
The action of Shakespeare's Richard II centres on the overthrow of a king and the installation of a usurper in his place. Male characters dominate the play in terms of numbers and stage time. It is an indication, paradoxically, of both the subordination of women in this political and military world as well as their refusal to be completely passive that all three major female characters are seen in roles of supplication before men. This paper considers the relation of power and language when one of these women, the Duchess of York, tries to persuade men to do her bidding. It examines the linguistic strategies she employs to gain ascendancy over them as well as those they use to assert their superiority. In addition to looking at how power is exerted through language, it also considers how power is reflected in language. The relevant parts of Act 5 Scene 2 and Act 5 Scene 3 of Richard II are analysed using adaptations of concepts from conversation analysis, Brown & Levinson's (1987) theory of politeness, and Culpeper's (1996) model of impoliteness.